Evaluation Impact of SIMVONI Implementation on Visitors' Perceptions in the Mpu Tantular Museum Using the IDT Method (Nusantara Science and Technology Proceedings, 2021)
The application of information technology in various fields is expected to have a positive impact that becomes its own competitiveness between organizations. However, in practice the implementation and updating of information technology does not mean that it will take place without obstacles. To maintain its existence, the Mpu Tantular Museum located in Sidoarjo City adopts virtual tour technology. The virtual tour technology is called the Indonesian Virtual Museum Application (SIMVONI). With the existence of several obstacles during the implementation process, an evaluation is needed to find out how well the system can run. This study aims to evaluate the impact of using SIMVONI on user perceptions using the Innovation and Diffusion Theory (IDT). IDT has five characteristics that serve as a general framework for determining the acceptance of an innovation, namely relative advantage, compatibility, complexity, trialability, and observability. Based on the results of the analysis carried out, it was found that the application of virtual tour technology at the Mpu Tantular Museum had a positive impact by making the museum still able to be visited without worrying about being exposed to the Covid-19 virus which was increasingly peaking. However, in the application of the Indonesian virtual museum application or SIMVONI, there are still some obstacles. The influential constraints are that some collections still have no detailed explanation, feature functions that are different from the usual, image resolution is still not good, and the UI display is not attractive.